A STELLAR DYNAMICAL MEASUREMENT OF THE BLACK HOLE MASS IN THE MASER GALAXY NGC 4258 - Siopis, C; Gebhardt, K; Lauer, T; Kormendy, J; Pinkney, J; Richstone, D; Faber, S; Tremaine, S; Aller, M; Bender, R; Bower, G; Dressler, A; et al. (2009)
We determine the mass of the black hole at the center of the spiral galaxy NGC 4258 by constructing axisymmetric dynamical models of the galaxy. These models are constrained by high spatial resolution imaging and long-slit spectroscopy of the nuclear region obtained with the Hubble Space Telescope, complemented by ground-based observations extending to larger radii. Our best mass estimate is M• = (3.3 ± 0.2) × 107 M⊙ for a distance of 7.28 Mpc (statistical errors only). This is within 15% of (3.82 ± 0.01) × 107 M⊙, the mass determined from the kinematics of water masers (rescaled to the same distance), assuming they are in Keplerian rotation in a warped disk. The construction of accurate dynamical models of NGC 4258 is somewhat compromised by an unresolved active nucleus and color gradients; the latter caused by variations in the stellar population and/or obscuring dust. Depending on how these effects are treated, as well as on assumptions about the ellipticity and inclination of the galaxy, we obtain black hole masses ranging from 2.4 × 107 M⊙ to 3.6 × 107 M ⊙. This spread is mainly due to uncertainties in the stellar mass profile inside the central 2″ (∼70 pc). Obscuration of high-velocity stars by circumnuclear dust (possibly associated with the masing disk) could lead to an underestimate of the black hole mass, which is hard to correct. These problems are not present in the ∼30 other black hole mass determinations from stellar dynamics that have been published by us and other groups; thus, the relatively close agreement between the stellar-dynamical mass and the maser mass in NGC 4258 enhances our confidence in the black hole masses determined in other galaxies from stellar dynamics using similar methods and data of comparable quality. © 2009. The American Astronomical Society. All rights reserved.